Back to the Great Ideas: Perennialisme sebagai Solusi Krisis Moral di Dunia Pendidikan - Adrian Saputra; Arif Hidayat; Herlini Puspika Sari (Dialektika : Jurnal Pendidikan Agama Islam, 2025)
This study examines the moral crisis occurring within contemporary educational settings, marked by declining honesty, responsibility, and respect among students. The purpose of this research is to analyze the relevance of perennialism as a philosophical foundation for strengthening moral and character education in the modern era. The study employs a library research method by reviewing books, scientific articles, and authoritative documents related to perennialism, morality, and Islamic education. Data were analyzed using content analysis through three stages: data reduction, thematic classification, and conceptual synthesis. The results indicate that perennialism emphasizes universal and timeless values, character formation through intellectual discipline, and the central role of teachers as moral guides. These principles align closely with the aims of Islamic education, which prioritizes the development of noble character. The study concludes that perennialism holds strong relevance in addressing moral degradation among students and recommends its integration into character-based curricula, teacher competence development, and Islamic educational practices. Keywords: perennialism, moral crisis, character education, Islamic education